Kualitas Laba Pada Sektor Infrastruktur Kontruksi Bangunan Dan Jasa Telekomunikasi Nirkabel Ditinjau Dari Struktur Modal Dan Ukuran Perusahaan - Yusuf Faisal; Nadya Putri Meiliana (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2024)
Purpose – This study aims to determine the effect of Capital Structure andCompany Size on Earnings Quality.Design/methodology/approach – This research uses quantitative data, thesample in this research is infrastructure sector companies in the buildingconstruction and wireless telecommunications services sub-sectors listed onthe Indonesia Stock Exchange in the 2018 – 2022 period, totaling 13companies. The analysis technique used to test the hypothesis is multipleregression analysis using Eviews 9 software.Findings – The results of this study indicate that the Capital Structurevariable has a positive and statistically insignificant effect on EarningsQuality, the Company Size variable has a positive and statisticallyinsignificant effect on Earnings Quality.Originality/value - This research discusses Profit Quality and otherfactors such as Capital Structure and Company Size which focuses oninfrastructure sector companies in the building construction and wirelesstelecommunications services sub- sectors.